Characterization of Asphalt Mixtures in Qatar - El Hussien, Osman; Hassan, Khaled E.; Al-Emadi, Khalid (Proceedings of the International Conference on Civil Infrastructure and Construction (CIC), 2020)
The State of Qatar went through a massive road construction program in the last decade as part of the ongoing development of its infrastructure and road transport network. Construction of roads in Qatar generally utilizes imported materials such as aggregate and binders as a result of the scarcity of local construction materials. Characteristics of asphalt mixtures are studied in this research program in order to evaluate mixtures properties in terms of aggregate packing, binder content, voids, mixture density, maximum density and Marshall Stability. Actual mixtures used in the Public Works Authority road projects were analyzed in the research program. Mixtures were prepared following the Qatar Construction Specifications (QCS, 2014). Combined aggregate gradations for different asphalt mixtures were compared with maximum density envelopes for different maximum aggregate sizes. Moreover, regression analysis was used to evaluate the strength of correlations established between different asphalt mixtures properties. The analysis of these mixtures is outlined in terms of general characteristics and consequently, recommendations are given to improve asphalt mixtures performance.